Tropical freedom : climate, settler colonialism, and Black exclusion in the age of emancipation - Asaka, Ikuko, 1975- (Duke University Press, 2017)
Ikuko Asaka examines emancipation's intersection with settler colonialism in North America, showing how emancipation efforts in the United States and present-day Canada were accompanied by attempts to relocate freed blacks to tropical regions, thereby conceiving freedom as a racially segregated condition based upon geography and climate.